2021
DOI: 10.1049/cds2.12042
|View full text |Cite
|
Sign up to set email alerts
|

MARPUF: physical unclonable function with improved machine learning attack resistance

Abstract: Nowadays, physical unclonable functions (PUFs) are emerging as one of the key building blocks for device authentication and key generation. Although PUF is very useful in the area of hardware security, it is vulnerable to machine learning modelling attacks (ML-MA) by modelling the challenge-response pairs (CRPs) behaviour. To this end, this study proposes a novel PUF named MARPUF, which gives good resistance to machine learning (ML) attacks. The study proposed a MARPUF design, where the mapping of CRPs is rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Generalized Neuro-Fuzzy Models (GNFM) [ 60 ], ANN model [ 61 ], ANFIS model [ 62 ], MLP-NN [ 63 ] [ 113 ], ELM algorithm [ 64 ] [ 90 ], M5 Model Tree [ 113 ], LS-SVR , MARS, ELM, WNN and GANN [ 66 ]. The DL model and ML model are applied in various domains such the COVID-19 analysis [ 114 ], proposed a novel method based on artificial intelligence (AI) to identify COVID-19 disease [ 115 ], developed genetically optimized Deep Neural Network [ 116 ], Tripathy et al [ 117 ] investigated the performance of MARPUF approach and it is found to be better resistant to such modelling attacks, image classification using deep learning [ 118 ], Artificial Intelligence approaches used to classifying various types of cancer [ 119 ], enhanced the grip functionality of myoelectric hands based on deep learning [ 120 ], and classifiers for on-line handwriting recognition based on SVM and KNN algorithms [ 121 ], and a survey for software fault prediction [ 122 ]. Singh et al [ 123 ] presented the efficient results and reliable algorithm for optimal design of water distribution networks.The literature summary of ML and EA are given in Table 5 .…”
Section: Literature Of Irrigation Schedulingmentioning
confidence: 99%
“…Generalized Neuro-Fuzzy Models (GNFM) [ 60 ], ANN model [ 61 ], ANFIS model [ 62 ], MLP-NN [ 63 ] [ 113 ], ELM algorithm [ 64 ] [ 90 ], M5 Model Tree [ 113 ], LS-SVR , MARS, ELM, WNN and GANN [ 66 ]. The DL model and ML model are applied in various domains such the COVID-19 analysis [ 114 ], proposed a novel method based on artificial intelligence (AI) to identify COVID-19 disease [ 115 ], developed genetically optimized Deep Neural Network [ 116 ], Tripathy et al [ 117 ] investigated the performance of MARPUF approach and it is found to be better resistant to such modelling attacks, image classification using deep learning [ 118 ], Artificial Intelligence approaches used to classifying various types of cancer [ 119 ], enhanced the grip functionality of myoelectric hands based on deep learning [ 120 ], and classifiers for on-line handwriting recognition based on SVM and KNN algorithms [ 121 ], and a survey for software fault prediction [ 122 ]. Singh et al [ 123 ] presented the efficient results and reliable algorithm for optimal design of water distribution networks.The literature summary of ML and EA are given in Table 5 .…”
Section: Literature Of Irrigation Schedulingmentioning
confidence: 99%